2003
DOI: 10.1097/01.mp.0000057236.96797.07
|View full text |Cite
|
Sign up to set email alerts
|

Calcifications in Ovary and Endometrium and Their Neoplasms

Abstract: In this study, we investigated the role of hormones in the pathogenesis of calcifications in ovary and in endometrium and their neoplasms of the gynecologic tract and assessed the anatomic location and incidence of these calcifications. The study consists of three parts designed to investigate the pathogenesis, the location, and the incidence of calcifications in ovary and endometrium and their neoplasms. In the first part, 79 female guinea pigs were divided into 10 groups, and different hormones, given weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Among different subtypes of ovarian cancer, calcified metastasis tends to occur more often in low-grade serous ovarian cancers [21,13,14,22,16,17,23]. The exact etiology of tumor calcification in ovarian cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different subtypes of ovarian cancer, calcified metastasis tends to occur more often in low-grade serous ovarian cancers [21,13,14,22,16,17,23]. The exact etiology of tumor calcification in ovarian cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology of tumor calcification in ovarian cancer is still unclear. It is hypothesized that multiple mechanisms may be involved in the pathogenesis of ovarian tumor calcifications, with dystrophic calcification developing secondary to degeneration of the epithelium or in areas of tumor necrosis or may be related to hormonal influence [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In that study, 96 (79%) of 122 patients with calcification had stages II and III disease, whereas 964 (85%) of 1134 patients without calcification had stages II and III disease. Likewise, in a study involving 35 ovarian cancers, Silva et al 17 found that all of the ovarian low-grade serous cancers had calcifications, whereas 80% of the serous borderline tumors had calcifications, and only 50% of the high-grade serous cancers contained calcifications. Also, Motohara et al 18 revealed the same result.…”
Section: Calcification and Histologic Stages In The Gynecological Tumorsmentioning
confidence: 93%
“…22 However, in the case of ovarian cancer, Cheng et al 23 17 found that calcification occurred predominantly in the stroma and could be induced by various hormones in guinea pigs; they suggested that this phenomenon was related to metabolic changes, which were secondary to stromal cell secretion, but not related to necrosis or degenerative changes. 17 The ultrastructural study of meningiomas by Tsuchida et al 24 found that collagen and vesicles secreted by tumor cells formed psammoma bodies. Similar view is also expressed in a study about ovarian cancer, Kiyozuka et al 25 reported that bone morphogenetic protein 2 and type IV collagen can promote the formation of psammoma bodies in ovarian cancer.…”
Section: Mechanism Of Formation Of Calcificationmentioning
confidence: 99%
“…(2001) found the formation of PBs in ovarian cancer was closely related to BMP-2 and type-IV collagen. Silva et al (2003) found hormone can affect the formation of PBs. Besides, nanobacteria may also get involved in the crystallization of PBs (Sedivy & Battistutti 2003;Hudelist et al 2004).…”
Section: Introductionmentioning
confidence: 99%